Perioperative mortality of pediatric surgical patients in a developing country: Incidence and Etiology - Chukwubuike Kevin Emeka (Global Journal of Perioperative Medicine - Peertechz Publications, 2021)
Background: Pediatric perioperative mortality is a measure of the quality and safety of surgical care in children. The aim of study was to evaluate the incidence, etiology and pattern of pediatric perioperative mortality (within 24 hours and within 30 days post-surgery) in a teaching hospital in Enugu, Nigeria.  Methods: This was a retrospective (STROBE) study of children that died within 30 days following surgery at the pediatric surgery unit of Enugu State University Teaching Hospital, Enugu, Nigeria.  Results: There were 2111 pediatric surgical procedures performed during the 5-year study period. Nineteen patients died within 24 hours of surgery which gave a mortality rate of 0.9%. Within 30th post-operative day, further 25 patients expired making it 44 mortalities in total, which correspond to 2.1% mortality rate. The median age of the patients was 2 years. Necrotizing enterocolitis, intussusception and typhoid intestinal perforation were the most common cause of mortality in neonates, infants and children greater than 1 year of age respectively. Overwhelming sepsis was the cause of mortality in most of the patients.  Conclusion: Generally, laparotomy for typhoid intestinal perforation was the most common surgical procedure that culminated in the patient's mortality. Specifically, necrotizing enterocolitis had the highest percentage of deaths.